The sensitivity of extended-spectrum beta-lactamase-producing Escherichia coli isolated from animal feces to antibiotics and Vietnamese garlic (Allium sativum L.) aqueous extracts in vitro: https://doi.org/10.12982/VIS.2024.054 - Bui Thi Le Minh; Nguyen Ho Quang Minh; Huynh Ngoc Trang (Veterinary Integrative Sciences, 2024)
This research was conducted to study the sensitivity of extended-spectrum beta-lactamase-producing Escherichia coli (ESBL-producing E. coli) isolated from pigs, dogs, chickens, and pheasants to antibiotics and extracts of Ly Son, Hai Duong, and Co Don garlic. The antibiotic susceptibility of bacteria was determined by the Kirby–Bauer test. Besides, the minimum inhibitory concentrations (MIC) and the minimum bactericidal concentration (MBC) of garlic extracts were determined by the dilution method. The results show that ESBL-producing E. coli isolated from chickens, dogs, pheasants, and pigs were resistant to 3/12, 5/12, 7/12, and 7/12 antibiotics, respectively. These strains were highly resistant to amoxicillin (100%), ampicillin (100%), and streptomycin (70-100%). Moreover, they were multi-resistant to 2-10 antibiotics. However, they were inhibited by Ly Son, Hai Duong, and Co Don garlic extracts with MIC 4.69-9.38 mg/mL, 2.35-18.75 mg/mL, and 4.69-18.75 mg/mL, respectively. MBC of Ly Son, Hai Duong, and Co Don garlic extracts ranged from 9.38 to >150 mg/mL. The ESBL-producing E. coli strains isolated from dogs were less sensitive to garlic extracts than those isolated from pigs, chickens, and pheasants. This study shows the potential of garlic to replace antibiotics in the prevention and treatment of animal diseases in the future.